Appraisal of the risk index as instrument to the stratification of the patient with acquired pneumonia in the community in the emergency department. - Dianelis Sierra Martínez; Orestes Fresneda Quintana; Luis Alberto Corona Martínez; María Caridad Fragoso Marchante; Iris González Morales; Caridad Hernández Abreus (Medisur)
The community acquired pneumonia is one of the most important health problems attended in our institution. In this article a critic analysis is made of an instrument for the stratification of the patients suffering of this disease in the urgency department, introduced as part of the guide of good correspondent clinic practices. Important deficiencies are identified that interfere in the application of this instrument and in its usage for the behaviour decisions taking by the assistance physician, of what comes the necessity of its improvement.